Dynamics of Access to Justice for Marginalized Communities in Urban Green-Space Utilization Conflicts During Ongoing Social and Environmental Transitions - Andes Robensyah; Citra Nasir; Nicat Kamran Mammadov (International Forum of Researchers and Lecturers, 2024)
Urban green-space conflicts have emerged as a significant challenge for marginalized communities, exacerbating existing social and environmental inequalities in cities undergoing rapid urbanization and environmental transitions. This study explores the dynamics of access to justice for marginalized groups in the context of urban green-space conflicts, focusing on the barriers they face and the enabling factors that improve their ability to access legal remedies. Through a socio-legal research design, data was collected using surveys, case reviews, and stakeholder interviews, which were analyzed to identify key physical, socio-economic, and institutional barriers that hinder equitable access to green spaces. Findings revealed that marginalized communities often experience physical barriers such as limited proximity to green spaces, socio-economic disparities that prevent them from accessing legal resources, and institutional constraints, including discriminatory urban planning policies. Despite these challenges, enabling factors such as legal aid networks, participatory forums, and inclusive urban planning policies emerged as crucial elements in improving access to justice for these communities. Moreover, the study examined the impact of social and environmental transitions, such as urbanization and climate change, on justice outcomes, showing that these transitions can either exacerbate or alleviate barriers depending on how policies are implemented. The study emphasizes the need for policy reforms that promote equity in urban planning and legal aid systems, ensuring that marginalized communities are included in decision-making processes. Future research should explore the impact of environmental justice policies in global contexts and investigate new legal frameworks to address the specific needs of vulnerable populations.